Océano Atlántico Sur, Islas Orcadas del Sur / compilación de levantamientos nacionales y extranjeros (Argentina. Ministerio de Marina, 1952)
1a edición 1952 Relief shown by spot heights and hachures. Depths shown by bathymetric isolines and soundings. Includes tidal and conversion tables. Coastal annotations. "Reproduction of Argentine chart, for official use only." "I.B. de Etchepare Cartógrafo" -- lower right margin. "117." Color; 1:200,000